Exotic Wild Plants, Cultural Adaptation, and Local Food Diversity in Tea Estate’s Buffer-Village (West Java, Indonesia): An Ethnobotanical Analysis - Shofia Az Zahra Aulia; Dede Mulyanto; Budiawati Supangkat Iskandar; Johan Iskandar (BRIN Publishing (Penerbit BRIN), 2026)
AULIA, S. A. Z., MULYANTO, D., ISKANDAR, B. S. & ISKANDAR, J. 2026. Exotic wild plants, cultural adaptation, and local food diversity in tea estate’s buffer-village (West Java, Indonesia): an ethnobotanical analysis. Reinwardtia 25(1): 13‒29. — This research examines the ethnobotanical knowledge of exotic wild plants utilized as complementary food in Tegallega hamlet, a part of the buffer village adjacent to a historic tea estate in West Java, Indonesia. Through semi-structured interviews and field surveys with 22 local informants, 42 exotic wild plants from 22 families were recorded, primarily from Asteraceae and Solanaceae. Predominant species were herbaceous neophytes introduced during or after European colonization, illustrating the historical impact of the Columbian Exchange and plantation practices. Leaves were the most commonly used plant part, frequently consumed as lalapan, an essential ingredient of Sunda cuisine. The community emphasizes readily accessible resources that require the least effort, consistent with optimal foraging theory, whereas gender roles markedly affect foraging practices—women generally collect plants near villages, whereas men tend to explore farther into the forest. The incorporation of these exotic wild plants into local diets underscores cultural adaptation and the enhancement of local knowledge. Using exotic wild plants sparingly can enhance conservation of native and endemic species, lessen the negative effects of invasive species, and create opportunities for ecotourism growth. This study highlights the interaction of historical, ecological, and cultural factors that influence local plant utilization practices.